Structural and defensive roles of angiosperm leaf venation network reticulation across an Andes–Amazon elevation gradient - Blonder, Benjamin (2018)
The network of minor veins of angiosperm leaves may include loops (reticulation). Variation in network architecture has been hypothesized to have hydraulic and also structural and defensive functions. We measured venation network trait space in eight dimensions for 136 biomass-dominant angiosperm tree species along a 3,300 m elevation gradient in southeastern Peru. We then examined the relative importance of multiple ecological and evolutionary predictors of reticulation. Variation in minor venation network reticulation was constrained to three axes. These axes described reconnecting vs. branching veins, elongated vs. compact areoles compact vs. elongated and low vs. high-density veins. Variation in the first two axes was predicted by traits related to mechanical strength and secondary compounds, and in the third axis by site temperature. Synthesis. Defensive and structural factors primarily explain variation in multiple axes of reticulation, with a smaller role for climate-linked factors. These results suggest that venation network reticulation may be determined more by species interactions than by hydraulic functions.